Co-production and Crisis Management: Overcoming COVID-19 and the Hunger Pandemics - Tolotti, Claudemara (2022)
The COVID-19 pandemic spread a multidimensional crisis of never-beforeexperienced proportions. Because of it, the situation in Brazil, which already had a scenario of great vulnerabilities and social disparities prior to the pandemic, was aggravated. The crisis and the fragility of the State's responses to the emerging demands were evidenced by the effort of the organized civil society to meet such demands. This study analyses the crisis management and co-production process during the COVID-19 pandemic in the city of Santa Maria-RS, in 2020, via the Mesa Brasil food bank program. The chosen research strategy was the case study. Data collection was carried out through documentary research, interviews and surveys with managers of participating institutions in the Mesa Brasil program. For the results, a content analysis technique was undertaken. The study allowed to conclude that crisis management, through co-participation, allows the understanding of the use of innovative and collective strategies as a means to overcome the emerging difficulties arising from crises in which social vulnerability increases. The research also explains how, in the specific context of the pandemic crisis, co-production of public services stood out for the adhesion of organizations, sharing responsibility and power in the production and delivery of public services to maintain food security and reduce food waste.